2018
DOI: 10.1111/jorc.12230
|View full text |Cite
|
Sign up to set email alerts
|

Bowel health in chronic kidney disease: Patient perceptions differ from clinical definitions

Abstract: It is common for patients with CKD to experience signs and symptoms of abnormal bowel health. There is a disconnect between patient perceptions and clinical definitions of normal or abnormal bowel health. Clinical care team members must carefully obtain and clarify patient-reported symptoms related to bowel function in order to help ensure recommendations and use of appropriate treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…We believe that the self-assessment of the severity of our patients' symptoms was influenced by the chronic maintenance of the intensity of the symptoms, that is, they became accustomed to feeling their symptoms so they cannot distinguish their severity unless a symptom is aggravated [ 42 ]. Age could be another factor of bias in the evaluation of symptoms, since although the questionnaire was carefully explained to each patient, some showed difficulty in evaluating the severity of their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the self-assessment of the severity of our patients' symptoms was influenced by the chronic maintenance of the intensity of the symptoms, that is, they became accustomed to feeling their symptoms so they cannot distinguish their severity unless a symptom is aggravated [ 42 ]. Age could be another factor of bias in the evaluation of symptoms, since although the questionnaire was carefully explained to each patient, some showed difficulty in evaluating the severity of their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…28 In fact, a recent cross-sectional study reported that more than half of patients with CKD (n ¼ 180) who had less frequent bowel movements (defined as bowel frequency of once every 4 to 6 days per week or less) with abnormal stool form and gastrointestinal symptom(s) perceived their bowel health as "normal" or "more normal than abnormal." 32 This finding clearly tells us that sole reliance on self-reporting of constipation in CKD may lead to the underestimation of the clinical problem, strongly suggesting the need for an active and standardized assessment of constipation in CKD by using subjective diagnostic tools such as the Rome criteria and the Bristol Stool Form Scale, which have yet rarely been used in clinical practice in the CKD population.…”
Section: Prevalence Of Constipation In Ckd Diagnostic Criteriamentioning
confidence: 99%
“…The burden of these GI symptoms in dialysis patients is poorly understood. Recent research suggests patients’ perceptions of their bowel health and clinical definitions of normal or abnormal bowel health are disconnected . The aim of this review is to summarize the current body of evidence describing the prevalence of GI symptoms reported in dialysis populations, as well as the assessment tools being used.…”
mentioning
confidence: 99%